PENGARUH JUMLAH PENDUDUK, JUMLAH PENGANGGURAN DAN TINGKAT PENDIDIKAN TERHADAP KETIMPANGAN PENDAPATAN - Matondang, Zulaika (Fakultas Ekonomi dan Bisnis Islam, 2018)
ABSTRACT This study was conducted to determine the effect of population, number of unemployed and the level of education on income inequality in the village of Palopat Maria, Padangsidimpuan Hutaimbaru District. The data processed in this study was primary data obtained through questionnaires in four environments in the village of Palopat Maria, Padangsidimpuan Hutaimbaru Subdistrict. The data obtained were analyzed using multiple linear regression that the equation was KP = - 0.007 + 0.023JP + 0.017JPNG + 0.003TP. Based on the analysis, the population, the number of unemployed and the level of education have affected 19.5 percent while the remaining 80.5 percent was influenced by other variables outside this research. The population have affected income inequality with the value of t count> t table (2,821> 1,664), the number of unemployed influences income inequality with the value of t count> t table (1,729> 1,644) and the level of education did not affect income inequality with the value of t count <t table (0.726 <1.664). The number of population, the number of unemployed and the level of education have affected income inequality with an F count> F table that is 6,454> 2,71 simultaneously.